THE ROLE OF NOTARY IN BANKING CREDIT AGREEMENTS IN CASE OF DEBTORS WANPRESTASI - Riza Zulfikar (Jurnal Scientia, 2022)
The position of a Notary, as a Public Official who draws up authentic deeds is very much needed in banking business activities, one of which is in making bank credit agreement deeds involving customers and banks, to guarantee the truth of the contents set forth in the bank credit agreement, so that the truth is not publicly no doubt. This study uses a normative juridical approach, namely legal research conducted by examining and examining secondary data in the form of positive law. While the research method used is analytical descriptive, namely systematically describing the facts and problems related to the role of a notary in a bank credit agreement in the event that a default debtor is linked to Law No. 10 of 1998 jo. Law No. 2 of 2014 concerning changes to the position of a notary. Notaries are very important in helping create legal certainty and protection for the public. This legal certainty and protection can be seen through the authentic deed he made as perfect evidence in court. Whereas the role of a notary in a deed of bank credit agreement made notarized by a notary is very beneficial for creditors if the debtor defaults on the strength of proof. In banking practice, making a credit agreement with a private deed can also provide guarantees for execution, because both notarial and private deeds are always followed by institutions with other collateral institutions whose deeds are executorial.